Body, sex, gender. Current Polish interpretive moment (Discourse of Law and Administration, 2023)
The paper aims to present Poland’s regulations concerning legal sex assignment and gender recognition in light of Poland’s social and political situation, which often leads to harmful and pathological decisions in the application of the law. To illustrate this, we will discuss the Polish legal situation regarding legal sex assignment and gender recognition. The authors will use the theoretical-legal concept of the interpretive moment to describe the evolution of the legal situation of individuals undergoing gender recognition procedures, despite the “letter of the law” remaining unchanged during the analyzed period. A change in the “letter” of Polish law is currently impossible due to the political factors. However, the activity of the fourth-wave feminism offers potential for a change in the interpretation of the existing regulations.
Keywords: legalizacja płci; legal sex assignment; gender recognition; interpretation of law